The Effects of T4 and A3/R Bacteriophages on Differentiation of Human Myeloid Dendritic Cells - Bocian, Katarzyna; Borysowski, Jan; Zarzycki, Michał; Pacek, Magdalena; Weber-Dąbrowska, Beata; Machcińska, Maja; Korczak-Kowalska, Grażyna; Górski, Andrzej (Frontiers in Microbiology, 2016)
Bacteriophages (phages) are viruses of bacteria. Here we evaluated the effects of T4 and A3R bacteriophages, as well as phage-generated bacterial lysates, on differentiation of human myeloid dendritic cells (DCs) from monocytes. Neither of the phages significantly reduced the expression of markers associated with differentiation of DCs and their role in the activation of T cells (CD40, CD80, CD83, CD86, CD1c, CD11c, MHC II, PD-L1, PD-L2, TLR2, TLR4, and CCR7) and phagocytosis receptors (CD64 and DEC-205). By contrast, bacterial lysate of T4 phage significantly decreased the percentages of DEC-205- and CD1c-positive cells. The percentage of DEC-205-positive cells was also significantly reduced in DCs differentiated in the presence of lysate of A3R phage. Thus while bacteriophages do not substantially affect differentiation of DCs, some products of phage-induced lysis of bacterial cells may influence the differentiation and potentially also some functions of DCs. Our results have important implications for phage therapy of bacterial infections because during infections monocytes recruited to the site of inflammation are an important source of inflammatory DCs.